Snakes of the Everglades Agricultural Area - Michelle L. Casler; Elise V. Pearlstine; Kenneth L. Krysko; Frank J. Mazzotti (EDIS)
This is a guide to common venomous and non-venomous snakes of southern Florida. This is document Cir 1462, one of a series in the Department of Wildlife Ecology and Conservation, University of Florida. Published December 2004.